Eksplorasi Pengaruh Beban Kerja pada Kesetiaan Karyawan - Chusnah, Arinal; Kholifah, Nanik; Astrella, Nathania Bayu; Fauzi, Amrul (Journal of Indonesian Psychological Science (JIPS), 2024)
ABSTRACT This study explores the influence of workload on employee loyalty at PT X, using a quantitative approach involving 108 employees as research subjects. The data collected were then analyzed using simple regression methods to examine the relationship between the variables of workload and employee loyalty. The results show a significant influence of workload on employee loyalty at PT X, with a correlation of 13.7% between workload and employee loyalty levels. This indicates that while workload has an impact on loyalty, there are 86.3% of other factors that also affect employee loyalty. This research is based on previous studies that highlight the importance of workload management in maintaining employee loyalty. Understanding that workload is only one of many factors influencing loyalty, PT X’s management is expected to take more comprehensive steps to improve employee loyalty, including considering other factors such as job satisfaction, recognition, and career development. The limitation of this study is its focus on the employees of PT X, with a sample size of 108 subjects. This research provides useful insights for companies in similar industries to manage workloads more effectively to increase employee loyalty. KEY WORDS: workload employee; loyalty; influence; workload impact